Physical and Chemical Characteristics and Classification of Soil in Plantation Land, Bareng Wonosalam, Jombang Regency - Dimas Prabowo Harliando; Dinna Hadi Sholikah; Maroeto Maroeto (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Soil is a fundamental factor influencing agricultural productivity, as it determines nutrient availability, water retention, and the long-term sustainability of farming systems. The Bareng Wonosalam District of Jombang Regency is a significant agricultural area with varied topography and intensive land use; however, comprehensive soil characterization in this region remains limited. This study aimed to analyze the physical and chemical characteristics of soils in plantation lands and classify them taxonomically to inform sustainable management. A representative plantation site in Pulosari Dua was selected using land-use and slope overlays. Five soil horizons (Ap, AB, Bt1, Bt2, BC) were described. Samples were analyzed for moisture content, texture, bulk density, pH (H₂O, KCl), electrical conductivity, organic carbon, total nitrogen, available phosphorus (Olsen, Bray), exchangeable cations (K, Na, Ca, Mg), cation exchange capacity (CEC), and base saturation (BS). Results showed moisture content of 6.2–20.8%, bulk density of 1.23–1.52 g/cm³, pH of 5.35–5.99, and organic carbon of 0.77–3.61%. Exchangeable K and Na were low (<0.60 cmol·kg⁻¹), while Ca ranged from 3.69–7.06 cmol·kg⁻¹. Textures were silty clay and clay, with BS of 53.5–117.1% and CEC of 9.15–12.93 cmol·kg⁻¹. The soils were classified as Typic Hapludalfs. Recommended practices include dolomite liming, potassium fertilization, structural amendments, and terracing. These actions are expected to enhance soil fertility, water retention, and plantation productivity by enabling targeted soil amendments, balanced nutrient application, and erosion control measures that directly address the identified limitations.